Rare SRRM2 mutation in neurodevelopmental disorders involving hyperphagia triggering severe obesity and other complication - Chang, Si-Hua; Wang, Xia; Jin, Jie-Yuan; Wang, Qin; Wu, Li-Ping (Frontiers in Medicine, 2025)
SRRM2 encodes a nuclear protein, with functions in pre-mRNA splicing and the formation of nuclear speckles via liquid-liquid phase separation. Despite its critical role in cellular function, the association between SRRM2 and neurodevelopmental disorders is not well-understood. In this study, we reported a case of a patient exhibiting developmental delay, intellectual disability, delayed language development, facial dysmorphism, macrocephaly, short hands and feet, hyperphagia, and hypotonia, which are similar to the characteristics of previously reported cases of SRRM2-associated neurodevelopmental disorders. Notably, the patient became overweight and subsequently developed several obesity-related complications due to uncontrolled hyperphagia. Employing whole exome sequencing (WES) and Sanger sequencing, we identified a novel missense mutation in SRRM2 (NM_016333: c.4661A > T, p.Q1554L). This mutation is classified as “Likely Pathogenic” based on the American College of Medical Genetics and Genomics (ACMG) guideline. Overall, this study contributes to the expanding spectrum of known mutations in SRRM2, enhances our understanding of its clinical implications, and offers crucial data for the diagnosis and management of affected individuals.